Effect of compound exercises on Some Kinetic Abilities in Some Bio kinematics Variables and the Characteristics of the Curve (Force - Speed) for hit/spike of High Volleyball for Youth Volleyball - Ali Naeem sultan1 , Ahmed Adnan Abd1, Asaad Flayyih Hasan 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The importance of the research is important to study the impact of compound exercises using light stimuliand sound stimuli as well as the use of rubber ropes and some training aids and to develop some of thekinetic abilities that help the athlete to integrate several kinetic skills in an orderly and sequential as wellas perform movements under changing conditions, to be able to face different Conditions and situationsexperienced during the game and well, as well as the development of indicators and function (force - speed),to reach the best mechanical conditions, and with the least decrease in speed and momentum, the researcherused the experimental method design one group The research sample was determined in a deliberate mannerand they are players of Al-Shatra Club of the volleyball youth in the district of Shatra and the number of (6)players. The results were analyzed by the analysis software using (SPSS, Logger Pro 3.10.1, Sigview v.2.8.0,Kinovea 0.8.25) to obtain the values of the BioKinmatk variables of the study. Technique of the skill of highhit/spike as a result of the development of internal strength using a The most important recommendationswere to emphasize the conduct of compound exercises, especially for muscles working on the joints of thehips, knees and ankles, as well as on the muscles working on the joints of the shoulders, elbows and wrists,as applied in the research for their importance in the development of some kinetic abilities and characteristicsof the curve. Power - speed.